Taxonomy of the genus Filatima Busck, 1939 (Lepidoptera: Gelechiidae) in China - Oh, Hyonju; Zhang, Xiuying; Li, Houhun (Zootaxa, 2023)
Eleven species of the genus Filatima from China are treated in the present paper. Four species, F. magnanella Oh & Li, sp. nov., F. nanjiangica Oh & Li, sp. nov., F. taxkorgana Oh & Li, sp. nov. and F. yanchiensis Oh & Li, sp. nov. are described as new. Three species, F. asiatica Sattler, 1961, F. angustipennis Sattler, 1961, and F. multicornuta Bidzilya & Nupponen, 2018, are newly recorded from China; F. pagicola (Meyrick, 1936) is redescribed, with female recorded for the first time. Images of adults and genitalia are illustrated except F. sciocrypta, and a key to all the known species in China is provided.